2011
DOI: 10.1097/igc.0b013e318218f270
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Medical Treatment of Clear Cell Ovarian Cancer

Abstract: This analysis suggests that lymphadenectomy has a strong prognostic role for clear cell ovarian cancer influencing disease-free survival and overall survival. The addition of paclitaxel to platinum-based chemotherapy does not affect the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…On a similar note, the role of lymphadenectomy from a therapeutic perspective is unclear. It is acknowledged that the presence of lymph node metastases is an independent prognostic factor however it is not associated with OS on multivariate analysis [7879808182]. Importantly, women undergoing fertility sparing surgery in OCCC did not show poorer survival than their non-OCCC counterparts [8384858687].…”
Section: Clear Cell Carcinomamentioning
confidence: 99%
“…On a similar note, the role of lymphadenectomy from a therapeutic perspective is unclear. It is acknowledged that the presence of lymph node metastases is an independent prognostic factor however it is not associated with OS on multivariate analysis [7879808182]. Importantly, women undergoing fertility sparing surgery in OCCC did not show poorer survival than their non-OCCC counterparts [8384858687].…”
Section: Clear Cell Carcinomamentioning
confidence: 99%
“…However, the role of lymphadenectomy remains unclear based on the therapeutic aspect. Several authors reported that lymph node metastasis is independent prognostic factor for CCC [7,8,15]. Magazzino et al analyzed 240 CCC retrospectively and reported as followed [15]: (1) Of 240 cases, 47.9% had lymphadenectomy and most of cases received platinum based chemotherapy after primary surgery.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Several authors reported that lymph node metastasis is independent prognostic factor for CCC [7,8,15]. Magazzino et al analyzed 240 CCC retrospectively and reported as followed [15]: (1) Of 240 cases, 47.9% had lymphadenectomy and most of cases received platinum based chemotherapy after primary surgery. (2) The cases who received lymphadenectomy had longer progression-free survival (PFS) than the cases who had no lymphadenectomy in stage I/II, III/IV and all stage (p = 0.0258, p = 0.00337, p = 0.0001).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Out of 240 patients with ovarian CCC [31], we identified 72 cases with recurrent disease (28% stage I-II and 72% stage III-IV at diagnosis).…”
Section: Methodsmentioning
confidence: 99%